Polytrauma in Older Adults Leads to Significantly Increased TIMP-1 Levels in the Early Posttraumatic Period - Mareen Braunstein; Thomas Kusmenkov; Wolf Mutschler; Christian Kammerlander; Wolfgang Böcker; Viktoria Bogner-Flatz (Journal of Immunology Research)
Background. Patients after polytrauma regularly suffer from posttraumatic immune system destabilization, which closely influences the further clinical development. Increasing age has recently been identified as an isolated risk factor for an adverse outcome after major trauma. Higher rates and intensity of acute inflammation following severe injury suggest that deregulated inflammation may contribute to these higher rates of posttraumatic morbidity and mortality in older adults. MMP-9 and TIMP-1 have been found to play a major role in posttraumatic immune disorder in a previous genome-wide mRNA analysis. Objective. The aim of this study was to evaluate the differences in serum protein dynamics in older and younger polytraumatized adults. Methods. Blood samples were drawn immediately within 90 minutes after trauma and subsequently after 6, 12, 24, 48, and 72 h. Serum levels of TIMP-1 and MMP-9 were quantified using ELISA. Age groups were divided according to a cutoff of 60 years. Results. 60 polytrauma patients (ISS>16) were included (<60 years, n=49; ≥60 years, n=11). Serum TIMP-1 and MMP-9 levels showed a highly significant serum dynamic in young and old polytrauma patients (p<0.001). Patients≥60 years showed significantly higher overall TIMP-1 levels (p=0.008). TIMP-1 levels showed a significant maximum after 72 h in the older study population. MMP-9 levels were nonsignificantly higher during the whole observational period in older polytrauma patients when compared to younger patients. Conclusion. The posttraumatic immune response is characterized by significantly higher TIMP-1 levels in older polytrauma patients. This significant association between TIMP-1 levels and patients’ age indicates a more extensive immune dysregulation following major trauma in older adults.